Effect of charge structure on deep-hole cumulative blasting to improve coal seam permeability - GUO De-yong; ZHANG Chao; ZHU Tong-gong; PAN Jing-jun (工程科学学报, 2018)
The charge structure is an important aspect of deep-hole cumulative blasting, and its influence on the blasting effect cannot be ignored; a reasonable charge structure can improve the rate of explosive energy utilization, thereby improving the blasting effect. In the study of the mechanism of deep-hole cumulative blasting in coal seam, the concentric decoupled charge structure is extensively analyzed. However, in the field test, the centers of the explosive charge and blast hole are offset because of the effect of gravity. Moreover, an eccentric decoupled charge structure is formed, which changes the decoupling coefficient around the blast hole and affects the blasting effect. This study focuses on the influence of the charge structure on improving coal seam permeability. The influence of the charge structure on the propagation characteristics of the explosion-induced stress wave and the partition of the explosion fracture was analyzed. A field experiment on coal seam deep-hole cumulative blasting was designed based on the gas geological conditions of the Ji group seam in Pingdingshan Coal Mine. Additionally, the influence of the charge structure on the horizontal and vertical directions of coal seam was discussed. Experimental results of deep-hole cumulative blasting in coal seam indicate that the charge structure has an influence on coal seam permeability. In the horizontal blasting area, the average increase in gas concentration is 52.78% after blasting. In the inspection holes located above and below the blast hole respectively, at a vertical distence of 1 m, after blasting, no blasting smoke escapes from the hole above the blast hole, but the blasting smoke escapes from the hole below the blast hole, which proves that the influence of the eccentric decoupled charge structure on coal seam below the blast hole is greater than that on coal seam above it. Moreover, the range of the fracture above the blast hole is smaller than that below the blast hole.